Intestinal parasites in children, in highly deprived areas in the border region of Chiapas, Mexico Parasitosis intestinal en niños, en áreas de alta marginación socioeconómica de la región fronteriza de Chiapas, México - Emma Marianela Morales-Espinoza; Héctor Javier Sánchez-Pérez; María del Mar García-Gil; Guadalupe Vargas-Morales; José Domingo Méndez-Sánchez; Margarita Pérez-Ramírez (Instituto Nacional de Salud Pública, 2003)
OBJECTIVE: To assess the prevalence of intestinal parasitic infections among children in highly deprived areas, and its possible association with demographic and socioeconomic indicators. MATERIAL AND METHODS: From March to September 1998 in a convenience sample of 32 communities of the border region of Chiapas, Mexico, selected at random based on the level of poverty and distance from the community to the nearest health care unit (<1 hour; 1 hour or more), one of every four households with children under 15 years of age was randomly selected to provide three stool samples from their children (n 1478). Bivariate and multivariate (generalized linear models for correlated binary data) analysis were performed. RESULTS: The global prevalence of intestinal parasitosis was 67% (95% confidence interval [CI] 64-70%). Sixty percent had multiple parasites. The prevalence of Entamoeba histolytica/E dispar was 51.2%, that of Giardia lamblia 18.3%, and that of Ascaris lumbricoides 14.5%. Multivariate analysis showed that age and speaking an indigenous language were significantly associated with the presence of E histolytica/ E dispar and Giardia lamblia. Source of water and lacking a refrigerator and electricity were associated with the presence of Ascaris lumbricoides. CONCLUSIONS: Measures should be taken to improve water quality, sewage disposal, and domestic hygiene. Furthermore, health programs should be established to promote breast-feeding, and education policies aimed at reinforcing the use of indigenous languages by physicians in the health services. OBJETIVO: Estimar la prevalencia de parasitosis intestinal en niños de zonas de alta marginación y su asociación con indicadores demográficos y socioeconómicos de interés. MATERIAL Y MÉTODOS: En una muestra de 1478 menores de edad, de entre 1 a 14 años, provenientes de 32 comunidades de la región fronteriza de Chiapas, México, de marzo a septiembre de 1998, se recolectaron tres muestras de heces fecales, seleccionadas aleatoriamente a partir del grado de marginación (alto y muy alto) del municipio al que pertenecen, y distancia de la unidad de salud más cercana a la comunidad (<1 hora; 1 hora o más). En una de cada cuatro viviendas con niños menores de 15 años de edad, seleccionadas aleatoriamente, se obtuvieron tres muestras de heces fecales de éstos. Se efectuaron análisis bivariados con la prueba de ji cuadrada y multivariados con modelos lineales generalizados. RESULTADOS: La prevalencia global de parasitosis fue de 67% (intervalo de confianza IC 95% 64-70%). Sesenta por ciento de los niños estaban multiparasitados. La prevalencia de Entamoeba histolytica/E dispar fue de 51.2%, de Giardia lamblia, 18.3% y de Ascaris lumbricoides, 14.5%. La mayor prevalencia de E histolytica/E dispar se asoció con la edad y hablar algún idioma indígena; la de Ascaris lumbricoides con el sitio de obtención de agua y la carencia de refrigerador y electricidad. CONCLUSIONES: Es necesario hacer intervenciones locales de salud (calidad del agua, sistemas de desagüe), programas de educación sanitaria (promoción de la lactancia materna y medidas higiénicas) y promoción del habla de idiomas indígenas entre los médicos de la región.